Dataset of temperature and relative humidity measurements in domestic refrigerators in Bangkok Thailand - Paviet-Salomon, Yvanne; Chaomuang, Nattawut; Potisuwan, Cheeraphat; Derens-Bertheau, Evelyne; Nukunudompanich, Methawee; Laguerre, Onrawee (My University, 2026)
This dataset provides detailed measurements of internal air temperature, product temperature, and relative humidity in domestic refrigerators in households in Bangkok, Thailand. Data were collected from 123 households using Freshliance TagPlus-TH data loggers installed both inside and outside the refrigerators. For each refrigerator, air temperature and relative humidity were monitored at five internal locations: top shelf, middle shelf, vegetable drawer, door shelf, and freezer compartment. In addition, the temperature of a meat-like test product placed on the middle shelf was recorded. Ambient air conditions surrounding each refrigerator were also measured to characterize the external thermal environment. Prior to deployment, all sensors were prepared and activated by the research team, with time zero (T0) defined at this stage. Participants were only required to place the sensors according to the provided instructions while minimizing disturbances to their usual refrigerator usage habits. The sensors remained inside the refrigerators for seven consecutive days, recording measurements every 5 minutes before being removed. Data collected during the first and seventh days of monitoring were excluded from the analysis to account for the uncertainty regarding the exact times at which consumers placed and removed the sensors. This exclusion also helped eliminate transient effects caused by the introduction of heat loads during sensor installation and removal, which are not representative of normal refrigerator operating conditions. Consequently, only the five-day dataset corresponding to stabilized operating conditions is presented. The dataset is provided as tab-delimited.txt files. File names identify both the refrigerator number (1–123) and refrigerator configuration, including single-door, two-door top-freezer, and two-door bottom-freezer models. An accompanying R script enables the generation of temperature and humidity profiles for each refrigerator over the 5-day monitoring period. A README document is also included and provides detailed descriptions of column names, sensor locations, and metadata associated with each measurement campaign. Temperature sensors have a resolution of 0.1°C over a range of −30°C to +70°C, and an expanded uncertainty of ±0.5°C (k = 2). Relative humidity sensors have a resolution of 0.1 % and an expanded uncertainty of ±3 % (k = 2). These uncertainty values are based on the manufacturer’s specifications, additional calibration could not be performed within the scope of this study due to the lack of suitable calibration equipment. This high-resolution dataset provides valuable insights into the thermal and hygrometric conditions of domestic refrigeration systems under real household usage conditions. The data may support a wide range of applications, including the assessment and optimization of refrigeration performance through analysis of temperature heterogeneity and thermal behavior inside refrigerating compartments, the evaluation of food safety and risks associated with domestic storage temperatures, the identification of potential temperature abuse conditions in challenge-test studies, the development of consumer recommendations, the development and validation of simplified thermal models and CFD simulations for predicting airflow and heat transfer within domestic refrigerators, studies related to energy consumption and food preservation, and the optimization of domestic refrigerator design parameters using CFD and artificial neural network approaches. The dataset is expected to provide valuable insights for researchers, stakeholders, and policymakers working on refrigeration technologies, food safety, and cold-chain management.
Keywords: Consumer; Domestic refrigeration; Food Storage; Monitoring